Mesoporous gold-copper hollow ultrathin nanosheet as well as preparation method and application thereof
Mesoporous gold-copper hollow ultra-thin nanosheets are prepared by oxidative etching, which solves the problem of difficulty in controlling the mesoporous structure and sheet thickness simultaneously in the existing technology, and achieves efficient photothermal conversion performance of gold-copper nanomaterials.
Patent Information
- Application Number
- CN202411435432.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing alloy nanomaterial preparation technology is difficult to simultaneously regulate the mesoporous structure and sheet thickness, thereby limiting the improvement of its photothermal conversion performance.
Mesoporous gold-copper hollow ultrathin nanosheets were prepared by oxidative etching, and by controlling the addition ratio of chloroauric acid and reaction conditions, the mesoporous structure and sheet thickness were effectively controlled.
It achieves simultaneous control of the mesoporous structure and lamellar thickness of gold and copper nanomaterials, significantly improves its photothermal conversion performance and provides higher photothermal conversion efficiency.
Smart Images

Figure CN119319254A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy nanomaterials, and specifically relates to a mesoporous gold-copper hollow ultrathin nanosheet and a preparation method and application thereof. Background Art
[0002] Alloy nanomaterials have always attracted people's attention among various metal nanomaterials. Since there are two or more metals in a single alloy nanomaterial, they can play a synergistic role, so they have important applications in catalysis, environmental science, biomedicine, energy, information technology, military equipment, aerospace and other fields. For example: CN118455537A discloses a preparation method and application of a coral-like AuPd alloy nanomaterial, CN111804929A discloses a method for preparing Pt-Cu nano-sheet alloy in water phase, and CN115254140A discloses a noble metal-non-noble metal alloy nanomaterial and its synthesis method. However, it is difficult for the existing preparation technology of alloy nanomaterials to effectively control the mesoporous structure and sheet thickness at the same time, thereby improving its performance.
[0003] Photothermal conversion materials are substances that can convert sunlight or other light sources into thermal energy. They usually have a high absorbance and can effectively absorb light energy and convert it into thermal energy. For example: CN113209307A discloses a nano-covalent organic framework material doped with Au&Ag alloy, and its preparation method and application. Gold-copper nanomaterials have good light absorption properties and are widely used in many fields such as electricity, magnetism and catalysis. The preparation of gold-copper nanoalloys with two-dimensional hollow structures has always been a research focus. How to effectively regulate the microstructure of gold-copper nanomaterials and improve their photothermal conversion performance is of great significance. To this end, the present invention is proposed. Summary of the invention
[0004] In view of the above-mentioned state of the prior art, the present invention provides mesoporous gold-copper hollow ultrathin nanosheets and a preparation method and application thereof.
[0005] The present invention prepares gold-copper nanosheets by means of oxidation etching, and simultaneously effectively regulates the mesoporous structure and sheet thickness of the gold-copper alloy nanomaterial, thereby improving its photothermal conversion performance.
[0006] The technical solution of the present invention is as follows:
[0007] The preparation method of mesoporous gold-copper hollow ultrathin nanosheets comprises the following steps:
[0008] (1) dissolving an organic amine, a quaternary ammonium salt surfactant, and a reducing agent in water, adding copper salt, reacting at a certain temperature for a period of time, separating and purifying by mechanical means, and redispersing in water;
[0009] (2) adding potassium salt, organic acid and an aqueous solution of a gold precursor to the product prepared in step (1), reacting at a certain temperature for a period of time, and separating and purifying by mechanical means to obtain a final product.
[0010] According to the present invention, preferably, in step (1), the organic amine is one of oleylamine, hexadecylamine, dodecylamine, octadecylamine and hexamethylenetetramine, and hexamethylenetetramine is most preferred.
[0011] According to the present invention, preferably, in step (1), the quaternary ammonium salt surfactant is one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, behenyltrimethylammonium bromide and behenyltrimethylammonium chloride, and cetyltrimethylammonium bromide is most preferred.
[0012] According to the present invention, preferably, in step (1), the reducing agent is one of sodium borohydride, citric acid, ascorbic acid and hydrazine hydrate, and ascorbic acid is most preferred.
[0013] According to the present invention, preferably, in step (1), the copper salt is one of copper chloride, copper bromide, copper sulfate, copper nitrate, and copper acetylacetonate, and most preferably copper nitrate.
[0014] According to the present invention, preferably, in step (1), the molar ratio of the organic amine, the quaternary ammonium salt surfactant, the reducing agent and the copper salt is (1.8-3.2):(0.5-1.5):(1.2-3.5):1.
[0015] According to the present invention, preferably, in step (1), the certain temperature is in the range of 10-95°C, more preferably 80°C.
[0016] According to the present invention, preferably, in step (1), the period of time is in the range of 0.5-10 hours, more preferably 3 hours.
[0017] According to the present invention, preferably, in step (2), the potassium salt is one of potassium chloride, potassium bromide, potassium iodide, potassium sulfate and potassium nitrate, and more preferably potassium chloride.
[0018] According to the present invention, preferably, in step (2), the organic acid is one of formic acid, acetic acid and oxalic acid, and more preferably acetic acid.
[0019] According to the present invention, preferably, in step (2), the gold precursor is one of chloroauric acid, bromoauric acid, gold chloride, gold bromide, and gold cyanide, and is more preferably chloroauric acid.
[0020] According to the present invention, preferably, in step (2), the molar ratio of potassium salt, organic acid and gold precursor is (30-2000): (1000-90000): 1;
[0021] Preferably, the molar ratio of the copper salt in step (1) to the gold precursor in step (2) is (10-1500):1.
[0022] According to the present invention, preferably, in step (2), the certain temperature is in the range of 10-95°C, and more preferably 25°C.
[0023] According to the present invention, preferably, in step (2), the period of time is in the range of 0.5-10 hours, more preferably 3 hours.
[0024] According to the present invention, preferably, in steps (1) and (2), the mechanical means is one of stirring, centrifugation, filtration, decantation, etc., and more preferably centrifugation.
[0025] According to the present invention, a mesoporous gold-copper hollow ultrathin nanosheet obtained by the above preparation method is also provided.
[0026] According to the present invention, there is also provided the use of the mesoporous gold-copper hollow ultrathin nanosheets obtained by the above preparation method as a photothermal conversion material.
[0027] Beneficial effects of the present invention:
[0028] 1. The preparation steps provided by the present invention are simple, the reactants are low-toxic, no hazardous chemicals are contained, water is used as a solvent, and the process is green and environmentally friendly;
[0029] 2. The present invention realizes the effective regulation of the mesoporous structure and sheet thickness of gold-copper nanosheets for the first time, expanding the limitations of the morphology and structure of the material;
[0030] 3. The mesoporous gold-copper hollow ultrathin nanosheets prepared by the present invention can be used as photothermal conversion materials. Their porous structure and ultrathin structure are conducive to the reflection and effective absorption of incident light, and can provide better photothermal conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a transmission electron microscope photograph of the product prepared in Example 1 of the present invention.
[0032] Figure 2 This is the X-ray diffraction spectrum of the product prepared in Example 1 of the present invention.
[0033] Figure 3 This is the UV-visible absorption spectra of the aqueous suspensions of the product prepared in Example 1 of the present invention and the comparative samples (copper nanosheets, gold-copper nanosheets).
[0034] Figure 4 Thermal imaging diagram of the aqueous suspension of the product prepared in Example 1 of the present invention and comparative samples (copper nanosheets, gold-copper nanosheets) and the change of water over time under laser irradiation.
[0035] Figure 5 Aqueous suspensions of the products prepared in Example 1 of the present invention and comparative samples (copper nanosheets, gold-copper nanosheets) and the temperature curves of water changing with time under laser irradiation.
[0036] Figure 6 The time constant (τ) and conversion efficiency (η) of the system heat transfer were determined by applying the linear time data of the cooling cycle for the aqueous suspension of the product prepared in Example 1 of the present invention.
[0037] Figure 7 This is the UV-visible absorption spectrum of the aqueous suspension of the product prepared in Example 1 of the present invention before and after laser irradiation. DETAILED DESCRIPTION
[0038] The present invention provides a mesoporous gold-copper hollow ultrathin nanosheet and a preparation method and application thereof. The preparation method of the mesoporous gold-copper hollow ultrathin nanosheet comprises the following steps:
[0039] (1) dissolving an organic amine, a quaternary ammonium salt surfactant, and a reducing agent in water, adding copper salt, reacting at a certain temperature for a period of time, separating and purifying by mechanical means, and redispersing in water;
[0040] (2) adding potassium salt, organic acid and an aqueous solution of a gold precursor to the product prepared in step (1), reacting at a certain temperature for a period of time, and separating and purifying by mechanical means to obtain a final product.
[0041] According to the present invention, in step (1), the organic amine acts as a structure directing agent.
[0042] In one or more preferred embodiments, the organic amine is one of oleylamine, hexadecylamine, dodecylamine, octadecylamine and hexamethylenetetramine, and hexamethylenetetramine is most preferred.
[0043] According to the present invention, in step (1), the quaternary ammonium salt surfactant acts as a capping agent on the surface of the nano copper flakes.
[0044] In one or more preferred embodiments, the quaternary ammonium salt surfactant is one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, behenyltrimethylammonium bromide, and behenyltrimethylammonium chloride, and cetyltrimethylammonium bromide is most preferred.
[0045] According to the present invention, in step (1), the reducing agent functions to reduce divalent copper ions to zero-valent copper.
[0046] In one or more preferred embodiments, the reducing agent is one of sodium borohydride, citric acid, ascorbic acid, and hydrazine hydrate, and is most preferably ascorbic acid.
[0047] In one or more preferred embodiments, the copper salt in step (1) is one of copper chloride, copper bromide, copper sulfate, copper nitrate, and copper acetylacetonate, and most preferably copper nitrate.
[0048] In one or more preferred embodiments, in step (1), the molar ratio of the organic amine, the quaternary ammonium salt surfactant, the reducing agent, and the copper salt is (1.8-3.2):(0.5-1.5):(1.2-3.5):1.
[0049] In one or more preferred embodiments, the certain temperature in step (1) is in the range of 10-95°C, more preferably 80°C.
[0050] In one or more preferred embodiments, the period of time in step (1) ranges from 0.5 to 10 hours, more preferably 3 hours.
[0051] In one or more preferred embodiments, the potassium salt in step (2) is one of potassium chloride, potassium bromide, potassium iodide, potassium sulfate and potassium nitrate, and more preferably potassium chloride.
[0052] According to the present invention, in step (2), the function of the organic acid is to oxidize and etch part of the copper element into monovalent or divalent copper.
[0053] In one or more preferred embodiments, the organic acid is one of formic acid, acetic acid and oxalic acid, and more preferably acetic acid.
[0054] In one or more preferred embodiments, the gold precursor in step (2) is one of chloroauric acid, bromoauric acid, gold chloride, gold bromide, and gold cyanide, and chloroauric acid is more preferably used.
[0055] In one or more preferred embodiments, the molar ratio of the potassium salt, the organic acid and the gold precursor in step (2) is (30-2000): (1000-90000): 1;
[0056] Preferably, the molar ratio of the copper salt in step (1) to the gold precursor in step (2) is (10-1500):1.
[0057] In one or more preferred embodiments, the certain temperature in step (2) is in the range of 10-95°C, more preferably 25°C.
[0058] In one or more preferred embodiments, the period of time in step (2) ranges from 0.5 to 10 hours, more preferably 3 hours.
[0059] In one or more preferred embodiments, in steps (1) and (2), the mechanical means is one of stirring, centrifugation, filtration, decantation, etc., more preferably centrifugation.
[0060] The present invention effectively regulates the mesoporous structure and sheet thickness of the gold-copper alloy nanomaterial by means of oxidation etching. The present invention regulates the size of the mesopore diameter by controlling the addition ratio of chloroauric acid. As the addition ratio of chloroauric acid increases, the mesopore diameter tends to increase. The sheet thickness is effectively controlled by controlling the reaction time or the addition ratio of the acid. As the reaction time increases and the addition ratio of the acid increases, the thickness of the obtained nanosheet tends to decrease.
[0061] According to the present invention, a mesoporous gold-copper hollow ultrathin nanosheet obtained by the above preparation method is also provided.
[0062] In one or more preferred embodiments, the mesoporous gold-copper hollow ultrathin nanosheets have a mesopore size of 4.0-11.0 nm and a nanosheet thickness of 7.0-15.0 nm.
[0063] According to the present invention, there is also provided the use of the mesoporous gold-copper hollow ultrathin nanosheets obtained by the above preparation method as a photothermal conversion material.
[0064] Example 1
[0065] 1.0g hexamethylenetetramine, 1.0g hexadecyltrimethylammonium bromide, and 1.0g ascorbic acid were dissolved in 100mL water, and 0.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 100mL water. 0.5g potassium chloride, 20.0g acetic acid, and 2mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0066] Example 2
[0067] 4.8g oleylamine, 1.0g hexadecyltrimethylammonium bromide, and 1.0g ascorbic acid were dissolved in 100mL water, and 0.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 100mL water. 0.5g potassium chloride, 20g acetic acid, and 2mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0068] Example 3
[0069] 2.0g of octadecylamine, 1.0g of hexadecyltrimethylammonium bromide, and 1.0g of ascorbic acid were dissolved in 100mL of water, and 0.5g of copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 100mL of water. 0.5g of potassium chloride, 20g of acetic acid, and 2mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0070] Example 4
[0071] 0.5g hexamethylenetetramine, 1.0g hexadecyltrimethylammonium chloride, 0.7g ascorbic acid were dissolved in 60mL water, 0.6g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. Purified by centrifugation, and redispersed in 50mL water. 0.2g potassium chloride, 1g acetic acid, and 1mL aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. Purified by centrifugation, and the final product was obtained.
[0072] Example 5
[0073] 0.1g hexamethylenetetramine, 0.1g octadecyltrimethylammonium bromide, and 0.3g ascorbic acid were dissolved in 15mL water, and 0.1g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 10mL water. 0.06g potassium chloride, 1.0g acetic acid, and 0.02mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0074] Example 6
[0075] 1.0g hexamethylenetetramine, 1.2g hexadecyltrimethylammonium bromide, 0.5g sodium borohydride were dissolved in 100mL water, 0.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. Purified by centrifugation, and redispersed in 100mL water. 0.5g potassium chloride, 20g acetic acid, and 2mL aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. Purified by centrifugation, and the final product was obtained.
[0076] Example 7
[0077] 0.2g hexamethylenetetramine, 0.2g hexadecyltrimethylammonium bromide, and 0.2g citric acid were dissolved in 30mL water, and 0.1g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 30mL water. 0.1g potassium chloride, 4.0g acetic acid, and 2mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0078] Example 8
[0079] 0.4g hexamethylenetetramine, 0.4g hexadecyltrimethylammonium bromide, and 0.4g ascorbic acid were dissolved in 70mL water, and 0.2g cupric chloride was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 40mL water. 0.2g potassium chloride, 6.0g acetic acid, and 5mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0080] Example 9
[0081] 0.6g hexamethylenetetramine, 0.6g hexadecyltrimethylammonium bromide, 0.7g ascorbic acid were dissolved in 80mL water, 0.3g copper sulfate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. Purified by centrifugation, and redispersed in 70mL water. 0.2g potassium chloride, 7.0g acetic acid, and 1mL aqueous solution of 50mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. Purified by centrifugation, and the final product was obtained.
[0082] Example 10
[0083] 3.0g hexamethylenetetramine, 3.0g hexadecyltrimethylammonium bromide, 5.5g ascorbic acid were dissolved in 500mL water, 1.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. Purified by centrifugation, and redispersed in 300mL water. 0.3g potassium chloride, 30g acetic acid, and 6mL aqueous solution of 50mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. Purified by centrifugation, and the final product was obtained.
[0084] Embodiment 11
[0085] 1.0g hexamethylenetetramine, 0.6g hexadecyltrimethylammonium bromide, and 0.9g ascorbic acid were dissolved in 30mL water, and 0.3g copper nitrate was added, and the mixture was reacted at 10 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 30mL water. 0.1g potassium chloride, 2.0g acetic acid, and 0.3mL of an aqueous solution of 10mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0086] Example 12
[0087] 1.5g hexamethylenetetramine, 1.5g hexadecyltrimethylammonium bromide, and 1.5g ascorbic acid were dissolved in 200mL water, 0.7g copper nitrate was added, and the mixture was reacted at 95 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 15mL water. 1.0g potassium chloride, 2.0g acetic acid, and 0.3mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0088] Embodiment 13
[0089] 1.0g hexamethylenetetramine, 1.0g hexadecyltrimethylammonium bromide, and 1.0g ascorbic acid were dissolved in 150mL water, and 0.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 0.5 hours. The mixture was purified by centrifugation and redispersed in 100mL water. 0.3g potassium chloride, 3.5g acetic acid, and 1mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0090] Embodiment 14
[0091] 5.0g hexamethylenetetramine, 3.0g hexadecyltrimethylammonium bromide, and 3.0g ascorbic acid were dissolved in 500mL water, and 1.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 10 hours. The mixture was purified by centrifugation and redispersed in 300mL water. 1.0g potassium chloride, 60.0g acetic acid, and 9mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0092] Embodiment 15
[0093] 0.5g hexamethylenetetramine, 0.6g hexadecyltrimethylammonium bromide, and 0.6g ascorbic acid were dissolved in 60mL water, and 0.3g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 60mL water. 0.2g potassium bromide, 6.0g acetic acid, and 0.6mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0094] Example 16
[0095] 1.0g hexamethylenetetramine, 1.0g hexadecyltrimethylammonium bromide, and 1.0g ascorbic acid were dissolved in 150mL water, and 0.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 100mL water. 1.2g potassium sulfate, 20.0g acetic acid, and 1.5mL of an aqueous solution of 50mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0096] Embodiment 17
[0097] 3.5g hexamethylenetetramine, 2.5g hexadecyltrimethylammonium bromide, 3.0g ascorbic acid were dissolved in 500mL water, 1.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 300mL water. 1.2g potassium chloride, 50.0g formic acid and 3mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0098] Embodiment 18
[0099] 2.0g hexamethylenetetramine, 2.0g hexadecyltrimethylammonium bromide, and 2.0g ascorbic acid were dissolved in 300mL water, 1.0g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 200mL water. 0.7g potassium chloride, 30.0g oxalic acid, and 1.5mL of an aqueous solution of 50mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0100] Embodiment 19
[0101] 10.0g hexamethylenetetramine, 10.0g hexadecyltrimethylammonium bromide, 11.0g ascorbic acid were dissolved in 1000mL water, 5.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 1000mL water. 30.0g potassium chloride, 800.0g acetic acid and 40mL of an aqueous solution of 50mM gold chloride were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0102] Embodiment 20
[0103] 1.0g hexamethylenetetramine, 1.0g hexadecyltrimethylammonium bromide, and 1.0g ascorbic acid were dissolved in 150mL water, and 0.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 100mL water. 1.0g potassium sulfate, 20.0g acetic acid, and 1mL of an aqueous solution of 50mM bromoauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0104] Embodiment 21
[0105] 1.0g hexamethylenetetramine, 1.0g hexadecyltrimethylammonium bromide, and 1.0g ascorbic acid were dissolved in 150mL water, and 0.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 50mL water. 0.3g potassium chloride, 20.0g acetic acid, and 2mL of an aqueous solution of 10mM chloroauric acid were added, and the mixture was reacted at 10 degrees Celsius for 3 hours. The mixture was purified by centrifugation and the final product was obtained.
[0106] Embodiment 22
[0107] 0.8g hexamethylenetetramine, 0.8g hexadecyltrimethylammonium bromide, 1.0g ascorbic acid were dissolved in 120mL water, 0.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. Purified by centrifugation, and redispersed in 50mL water. 0.6g potassium chloride, 15.0g acetic acid, and 2mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 95 degrees Celsius for 3 hours. Purified by centrifugation, and the final product was obtained.
[0108] Embodiment 23
[0109] 1.2g hexamethylenetetramine, 1.6g hexadecyltrimethylammonium bromide, 1.2g ascorbic acid were dissolved in 120mL water, 0.4g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. Purified by centrifugation, and redispersed in 40mL water. 1.0g potassium chloride, 25.0g acetic acid, and 0.2mL aqueous solution of 10mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 0.5 hours. Purified by centrifugation, and the final product was obtained.
[0110] Embodiment 24
[0111] 0.2g hexamethylenetetramine, 0.2g hexadecyltrimethylammonium bromide, and 0.2g ascorbic acid were dissolved in 30mL water, and 0.1g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 20mL water. 0.1g potassium chloride, 10.0g acetic acid, and 0.2mL of an aqueous solution of 10mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 10 hours. The mixture was purified by centrifugation and the final product was obtained.
[0112] Embodiment 25
[0113] 1.0g hexamethylenetetramine, 1.0g hexadecyltrimethylammonium bromide, and 1.0g ascorbic acid were dissolved in 150mL water, and 0.4g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was separated and purified by decantation, and redispersed in 80mL water. 0.2g potassium chloride, 5.0g acetic acid, and 2mL of an aqueous solution of 10mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation, and the final product was obtained.
[0114] Embodiment 26
[0115] 1.0g hexamethylenetetramine, 1.0g hexadecyltrimethylammonium bromide, 1.0g ascorbic acid were dissolved in 150mL water, 0.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was separated and purified by filtration, and redispersed in 100mL water. 0.3g potassium chloride, 20.0g acetic acid, and 2mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by centrifugation, and the final product was obtained.
[0116] Embodiment 27
[0117] 0.5g hexamethylenetetramine, 0.5g hexadecyltrimethylammonium bromide, 1.0g ascorbic acid were dissolved in 150mL water, 0.5g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. The mixture was purified by centrifugation and redispersed in 100mL water. 0.3g potassium chloride, 20.0g acetic acid and 2mL of an aqueous solution of 20mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. The mixture was purified by decantation and the final product was obtained.
[0118] Embodiment 28
[0119] 1.0g hexamethylenetetramine, 1.0g hexadecyltrimethylammonium bromide, 1.5g ascorbic acid were dissolved in 150mL water, 1.0g copper nitrate was added, and the mixture was reacted at 80 degrees Celsius for 3 hours. Purified by centrifugation, and redispersed in 100mL water. 1.2g potassium chloride, 30.0g acetic acid, and 2mL aqueous solution of 50mM chloroauric acid were added, and the mixture was reacted at 25 degrees Celsius for 3 hours. Purified by filtration, and the final product was obtained.
[0120] Test Example 1
[0121] The transmission electron microscope photo of the final product prepared in Test Example 1 is as follows: Figure 1 As shown. Figure 1 It can be seen that the mesopore size of the mesoporous gold-copper hollow ultrathin nanosheets is 4.0-11.0 nm, and the thickness of the nanosheets is 7.0-15.0 nm.
[0122] Test Example 2
[0123] The X-ray diffraction spectrum of the final product mesoporous gold-copper hollow ultrathin nanosheets prepared in Test Example 1. Figure 2 As shown. Figure 2 It can be seen that by comparing with the Au and Cu standard PDF cards, the mesoporous gold-copper hollow ultrathin nanosheet crystal structure is composed of a copper face-centered cubic structure and a gold-copper alloy face-centered cubic structure. The EDS elemental composition test shows that the copper / gold atomic ratio is 2 / 1.
[0124] Test Example 3
[0125] The UV-visible absorption spectrum of the final product mesoporous gold-copper hollow ultrathin nanosheets prepared in Test Example 1. Figure 3 As shown. Figure 3 It can be seen that the gold-copper hollow ultrathin nanosheets water suspension has a strong absorbance at a wavelength of 800-1100nm. The comparison samples are gold-copper nanosheets and copper nanosheets, which have no mesopores and are dozens of times thicker than the gold-copper hollow ultrathin nanosheets.
[0126] Test Example 4
[0127] The photothermal conversion performance of the final product mesoporous gold-copper hollow ultrathin nanosheets prepared in Example 1 was tested. Figure 4 , 5, 6, and 7. Using a wavelength of 808 nm and a power density of 1 W / cm 2 Laser irradiation of mesoporous Au-Cu hollow ultrathin nanosheets in water suspension, Figure 4 It can be seen that as the laser irradiation time increases, the temperature of the sample suspension gradually increases. Figure 5 It can be seen that after 10 minutes of irradiation, the temperature of the gold-copper hollow ultrathin nanosheet suspension increased from 23 degrees Celsius to 48 degrees Celsius. Compared with the comparison samples of gold-copper nanosheets, copper nanosheets and water, the suspension of the product of the present invention heated up faster after laser irradiation and reached a higher temperature in 10 minutes. Figure 6 It can be seen that the photothermal conversion efficiency (η) of the mesoporous gold-copper hollow ultrathin nanosheets is 59.4%. Figure 7 It can be seen that the absorbance of the mesoporous gold-copper hollow ultrathin nanosheets increases slightly before and after laser irradiation, indicating that they have good stability under laser irradiation environment.
Claims
1. A method for preparing mesoporous gold-copper hollow ultrathin nanosheets, comprising the following steps: (1) dissolving an organic amine, a quaternary ammonium salt surfactant, and a reducing agent in water, adding copper salt, reacting at a certain temperature for a period of time, separating and purifying by mechanical means, and redispersing in water; (2) adding potassium salt, organic acid and an aqueous solution of a gold precursor to the product prepared in step (1), reacting at a certain temperature for a period of time, and separating and purifying by mechanical means to obtain a final product.
2. The method for preparing the mesoporous gold-copper hollow ultrathin nanosheet according to claim 1, characterized in that: In step (1), the organic amine is one of oleylamine, hexadecylamine, dodecylamine, octadecylamine and hexamethylenetetramine; Preferably, in step (1), the quaternary ammonium salt surfactant is one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, behenyltrimethylammonium bromide and behenyltrimethylammonium chloride; Preferably, in step (1), the reducing agent is one of sodium borohydride, citric acid, ascorbic acid and hydrazine hydrate, and ascorbic acid is most preferred.
3. The method for preparing the mesoporous gold-copper hollow ultrathin nanosheet according to claim 1, characterized in that: In step (1), the copper salt is one of copper chloride, copper bromide, copper sulfate, copper nitrate and copper acetylacetonate.
4. The method for preparing the mesoporous gold-copper hollow ultrathin nanosheet according to claim 1, characterized in that: In step (1), the molar ratio of the organic amine, the quaternary ammonium salt surfactant, the reducing agent and the copper salt is (1.8-3.2):(0.5-1.5):(1.2-3.5):
1.
5. The method for preparing the mesoporous gold-copper hollow ultrathin nanosheet according to claim 1, characterized in that: In step (1), the certain temperature ranges from 10 to 95° C.; Preferably, in step (1), the period of time is in the range of 0.5-10 hours.
6. The method for preparing the mesoporous gold-copper hollow ultrathin nanosheet according to claim 1, characterized in that: In step (2), the potassium salt is one of potassium chloride, potassium bromide, potassium iodide, potassium sulfate, and potassium nitrate; Preferably, in step (2), the organic acid is one of formic acid, acetic acid and oxalic acid; Preferably, in step (2), the gold precursor is one of chloroauric acid, bromoauric acid, gold chloride, gold bromide, and gold cyanide.
7. The method for preparing the mesoporous gold-copper hollow ultrathin nanosheet according to claim 1, characterized in that: In step (2), the molar ratio of potassium salt, organic acid and gold precursor is (30-2000): (1000-90000): 1; Preferably, the molar ratio of the copper salt in step (1) to the gold precursor in step (2) is (10-1500):
1.
8. The method for preparing the mesoporous gold-copper hollow ultrathin nanosheet according to claim 1, characterized in that: In step (2), the certain temperature ranges from 10 to 95° C.; Preferably, in step (2), the period of time is in the range of 0.5-10 hours.
9. According to the present invention, there is also provided a mesoporous gold-copper hollow ultrathin nanosheet obtained by the above preparation method.
10. According to the present invention, there is also provided the use of the mesoporous gold-copper hollow ultrathin nanosheets obtained by the above preparation method as a photothermal conversion material.
Citation Information
Patent Citations
Method for preparing Pt-Cu nano sheet-like alloy from aqueous phase
CN111804929A
Nano covalent organic framework material doped with Au&Ag alloy as well as preparation method and application of nano covalent organic framework material
CN113209307A
Preparation method and application of coralline AuPd alloy nano material
CN118455537A
Preparation method and application of AuCu alloy adjustable in surface atomic ratio
CN110125436A
Composite nano material, preparation method and catalyst
CN113813972A